New attitudes and clinical behaviors on COVID-19 of Lima dentists - Leon Rios, Ximena Alejandra (2023)
Objective. To determine the association between new attitudes and clinical behaviors on COVID-19, according to the demographic characteristics of dentists in Lima. Methods. An observational, analytical, cross-sectional study was carried out with a sample of 206 dentists residing in Lima. The new clinical attitudes and behaviors were evaluated using the instrument validated by Duruk. In addition, other variables were recorded, such as sex, age, main institution and speciality. The chi-square test was used to determine the association of qualitative variables, establishing a significance level of p < 0.05. Results. A large group of the respondents used at least some preventive measure in their patients and received information through offcial websites. Statistically significant associations were found between the new attitudes and clinical behaviors of the dentists and their demographic characteristics. A relationship was found between sex and the use of frequent ventilation in closed environments (p = 0.015) and with changes in patient admission (p = 0.001). Likewise, a relationship was established between the main work institution with the avoidance of procedures with aerosol exposure (p = 0.044) and changes in patient admission (p = 0.001). Conclusions. Correlations were found between new clinical attitudes and behaviors and some demographic characteristics of the surveyed dentists.